Idiopathic Pulmonary Fibrosis: Aging, Mitochondrial Dysfunction, and Cellular Bioenergetics - Zank, Daniel C.; Bueno, Marta; Mora, Ana L.; Rojas, Mauricio (Frontiers in Medicine, 2018)
At present, the etiology of idiopathic pulmonary fibrosis (IPF) remains elusive. Over the past two decades, however, researchers have identified and described the underlying processes that result in metabolic dysregulation, metabolic reprogramming, and mitochondrial dysfunction observed in the cells of IPF lungs. Metabolic changes and mitochondrial dysfunction in IPF include decreased efficiency of electron transport chain function with increasing production of reactive oxygen species, decreased mitochondrial biogenesis, and impaired mitochondrial macroautophagy, a key pathway for the removal of dysfunctional mitochondria. Metabolic changes in IPF have potential impact on lung cell function, differentiation, and activation of fibrotic responses. These alterations result in activation of TGF-β and predispose to the development of pulmonary fibrosis. IPF is a disease of the aged, and many of these same bioenergetic changes are present to a lesser extent with normal aging, raising the possibility that these anticipated alterations in metabolic processes play important roles in creating susceptibility to the development of IPF. This review explores what is known regarding the cellular metabolic and mitochondrial changes that are found in IPF, and examines this body of literature to identify future research direction and potential points of intervention in the pathogenesis of IPF.